TECHNOLOGY-BASED EDUCATIONAL SUPERVISION MANAGEMENT TO ENHANCE LEARNING EFFECTIVENESS - Irda Suriani; Anggi Anggi; Ahdia Riskon; Anggi Prasutio Marbun; Wahid Lubis; Rizki Purnawan; Rahma Dayani Hasibuan; Widia Permata Sari Siregar; Khomaria Harahap; Devita Sari Sipahutar (Literasi Nusantara, 2026)
This study aims to analyze the implementation of technology-based educational supervision management and its contribution to enhancing learning effectiveness in secondary schools. The research employs a qualitative descriptive approach through a comprehensive review of relevant literature on educational supervision, digital technology integration, and instructional management. The findings indicate that technology-based supervision improves the efficiency of planning, monitoring, evaluation, and feedback processes. Digital platforms facilitate continuous communication between school leaders and teachers, enable real-time monitoring of instructional practices, and support data-driven decision-making for professional development. Furthermore, the integration of digital tools into supervision activities encourages teachers to adopt innovative teaching strategies, strengthens instructional quality, and promotes sustainable professional growth. The study concludes that technology-based educational supervision management plays a significant role in improving learning effectiveness by creating a more systematic, transparent, collaborative, and responsive supervision process. Successful implementation, however, depends on adequate technological infrastructure, digital competence among educators, and strong institutional support.